Analisis Karakteristik Kecelakaan di Ruas Jalan Gadjah Mada Kabupaten Jember - Tiara Ayu Rahmawaty; Willy Kriswardhana; Wiwik Yunarni Widiarti; Sonya Sulistyono (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
Gadjah Mada Road is one of the main roads in the Jember and is an urban road that has high activity. Therefore, it has a history of traffic accidents. The purpose of this study was to determine the characteristics of accidents at the KFC-Sentot Prawirodirdjo intersection and Sentot Prawirodirdjo-Argopuro intersection, to determine the EAN (Equivalent Accident Number) value, and the accident rate. Accident characteristics were analyzed based on the number of accidents obtained from the Integrated Road Safety Management System (IRSMS) on weekdays and weekends, EAN value was calculated to estimate the accident weight, and accident rate to determine the level of accident vulnerability. From the analysis, the results obtained from 2017-2018 in the KFC-Sentot Prawirodirdjo intersection have 87 accidents and the Sentot Prawirodirdjo-Argopuro intersection in 2014-2018 there were 228 accidents. Most of the accident victims at the KFC-Simpang Sentot Prawirodirdjo intersection were minor injuries and material losses. Vehicles that often involved in accidents were motorcycles. The time of the accident that often occurs was the night (17.01-21.00). The dominant type of accident is a crash when overtaking from the right. Furthermore, for the Sentot Prawirodirdjo-Argopuro intersection, most accident victims were minor injuries and material losses. The vehicle that is often involved is a motorcycle. The time of the most dominant accident is morning (05.01-09.00), and the type of accident that dominates is crash when overtaking from the right.